The effect of megadosis of iron consumption on the absorption of zinc and copper in rat (Rattus rattus) determined in situ - Sukarti Moeljopawiro Sukarti Moeljopawiro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
Oral administration of iron pill must be at an accurate dosis because high consumption of iron could impair the absorption of other minerals especially bivalent metals. Therefore, the objective of this study was to evaluate the effect of megadosis consumption of iron on the absorption of zinc and copper. The inorganic minerals were used in this study. The amount of mineral absorption was determined in situ. Forty male weanling rats were used in, this study. Rats were divided into 8 groups of 5, two groups for each treatment. Four ratios of Fe, Zn and Cu were used in this study (Fe : Zn : Cu = 5 : 1 : 1; 10 : 1 : 1; 20 : 1 : 1 and 50 ; 1 : 1). The amount of mineral absorption was determined using in vivo intestinal perfusion, and two perfusion rates were used 0.5 ml/minute and 0.33 ml/minute. It was found that high iron consumption (50 : 1 : 1) could impair the zinc absorption at perfusion rate of 0.33 ml/minute and no zinc absorption occur at perfusion rate of 0.5 ml/minute. However, this high iron consumption did not influence the copper absorption both at perfusion rate of 0.5 ml/minute and 0.33 ml/minute. It can be concluded that high consumption of iron could impair the zinc absorption but not copper absorption.Key words : iron - zinc - copper - mineral absorption - in situ perfusion